Poética y Política sin Mundo - Rubio, Antonio Méndez (eLyra, 2018)
The relationship between poetics and politics is fractured due to being in a world equally fractured, in crisis. The resulted split moves poetics and politics towards a so-called (and often sublimated) relationship between ethics and aesthetics. In fact, it seems that poeisis and politeia are learning to survive in a sterile and confine solitude. In the limits of a subjectivity bored by new ways of pressure, this article seeks to answer to this question: what are the options for creativity to become a new manner of communication and, most importantly, a critical link? The attempted answer will consider the current theoretical and practical circumstances of the relationship between poetics and politics, between solitude and community.